Analysis of long-lived C. elegans daf-2 mutants using serial analysis of gene expression - Julius Halaschek-Wiener; Jaswinder Khattra; Sheldon McKay; Anatoli T. Pouzyrev; Jeff Stott; George Yang; Robert A. Holt; Steven J.M. Jones; Marco A. Marra; Angela Brooks‐Wilson; Donald L Riddle (2005)
We have identified longevity-associated genes in a long-lived Caenorhabditis elegans daf-2 (insulin/IGF receptor) mutant using serial analysis of gene expression (SAGE), a method that efficiently quantifies large numbers of mRNA transcripts by sequencing short tags. Reduction of daf-2 signaling in these mutant worms leads to a doubling in mean lifespan. We prepared C. elegans SAGE libraries from 1, 6, and 10-d-old adult daf-2 and from 1 and 6-d-old control adults. Differences in gene expression between daf-2 libraries representing different ages and between daf-2 versus control libraries identified not only single genes, but whole gene families that were differentially regulated. These gene families are part of major metabolic pathways including lipid, protein, and energy metabolism, stress response, and cell structure. Similar expression patterns of closely related family members emphasize the importance of these genes in aging-related processes. Global analysis of metabolism-associated genes showed hypometabolic features in mid-life daf-2 mutants that diminish with advanced age. Comparison of our results to recent microarray studies highlights sets of overlapping genes that are highly conserved throughout evolution and thus represent strong candidate genes that control aging and longevity.